Synthesis of Carbazole Based Co-polymers Containing Thienothiophene and Benzothiadiazole Units in a Direct Arylation Scheme. Issue 9 (November 2016) - Sarjadi, Mohd Sani; Iraqi, Ahmed
The photovoltaic effect can be used to harvest energy from sunlight, enabling a cleaner approach to generating energy. Organic photovoltaics based on polymers are an attractive replacement of expensive, high energy consuming silicon solar cells. However, the limitations of efficiency have prevented industrial application, and polymer-based solar cells remain uncompetitive. Thus, optimisation of efficiency is required before potential application of these devices. In this work, the polymers were synthesised by direct arylation, in order to investigate its suitability for application in photovoltaic cell. Morphological, spectroscopic and charge-transport measurements are used to investigate the influence of either the dithienyl or thienothiophene moieties on the structure and photophysical properties of the copolymer rationalise the solar cell characteristics. The polymers obtained were characterised using 1 H-NMR, 13 C-NMR, IR, UV and thermal gravimetric analysis. The absorption spectral, thermal, electrochemical and photovoltaic properties of the random copolymers were investigated. Finally, a new series of carbazole-based dithienyl or thienothiophene polymers was successfully synthesised and characterised.